2014
DOI: 10.1103/physrevb.89.205304
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous x-ray scattering study of the growth of inverted quantum hut structures in a Si-Ge superlattice emitting strong photoluminescence

Abstract: The growth process of germanium inverted quantum hut (IQH) structures, which are embedded in a silicon lattice, has been studied using anomalous x-ray scattering techniques. These self-assembled IQH structures exhibit strong photoluminescence (PL) although the number density of the huts is rather small. We show here that these IQH structures form by the intermixing of germanium with previously deposited silicon producing an intriguing composition variation that keeps the out-of-plane lattice parameter of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The process of the formation of IQH structures has been studied in detail by anomalous x-ray scattering for a similar Si/Ge superlattice structure [13]. It was shown that the deposited Ge layer relaxes strain by diffusing into the previously deposited lower Si layer to form a Si 0.6 Ge 0.4 wet layer and IQH structure form below it.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of the formation of IQH structures has been studied in detail by anomalous x-ray scattering for a similar Si/Ge superlattice structure [13]. It was shown that the deposited Ge layer relaxes strain by diffusing into the previously deposited lower Si layer to form a Si 0.6 Ge 0.4 wet layer and IQH structure form below it.…”
Section: Methodsmentioning
confidence: 99%
“…These quantum dots with tip pointing up are then overgrown by Si capping in order to avoid oxidation and surface recombination of exciton for the development of a Si based optical material. Recent experiments have shown that at low temperature growth of Si/Ge multi-layers, inverted quantum hut (IQH) structures form below the Ge wet-layer with their apex pointing towards Si substrate [11][12][13]. X-ray diffraction results [13] have shown that at low growth temperature (< 500…”
Section: Introductionmentioning
confidence: 99%
“…3(a) was collected with sample to detector distance of 100 cm and the width of Au (111) diffraction peak was 0.45 0 where contribution of beam divergence can be maximum 0.025 0 . It may be noted that the measured width 26 of a typical single crystal diffraction peak at these beamlines in same configuration is 0.03 0 . As the diffraction peaks of Au nanoparticles are quite broad, we reduced the sample to detector distance to 14 cm to enhance peak-to-background ratio for monitoring the chemical reaction as a function of time.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, at the tip values of || = 0 and ⊥ = −0.5% are observed. In the original publication, a further measurement was used to confirm these findings [25].…”
Section: Tsmentioning
confidence: 99%
“…CTR scattering and GID measurements have been used to determine the structure and the stress in self organized inverted quantum huts which arise when growing thin germanium silicon multilayer stacks with molecular beam epitaxy at low temperatures, as published by M. Sharma et al [25]. Germanium and silicon crystallize in a cubic diamond structure with lattice constants Si = 5.431 Å and Ge = 5.658 Å.…”
Section: X-ray Studies Of Inverted Quantum Hut Structures In a Si-ge mentioning
confidence: 99%